Modulation of oxidative stress, inflammation, autophagy and expression of Nrf2 in hippocampus and frontal cortex of rats fed with açaí-enriched diets. (28th May 2017) - Poulose, Shibu M.; Bielinski, Donna F.; Carey, Amanda; Schauss, Alexander G.; Shukitt-Hale, Barbara
Abstract : Objective: Açaí ( Euterpe spp .), an exotic palm fruit, has recently emerged as a promising source of natural antioxidants with wide pharmacological and nutritional value. In this study, two different species of açaí pulp extracts, naturally grown in two distinct regions of the Amazon, namely, Euterpe oleracea Mart. (habitat: Brazilian floodplains of the Amazon) and Euterpe precatoria Mart. (habitat: Bolivian Amazon), were studied for their effects on brain health and cognition. Methods: Neurochemical analyses were performed in critical brain regions associated with memory and cognition of 19-month-old açaí-fed rats, in whom the cognitive benefits of açaí had been established. Results: Results indicated significant reductions ( P< 0.05) in prooxidant NADPH-oxidoreductase-2 (NOX2) and proinflammatory transcription factor NF-κB in açaí-fed rats. Measurement of Nrf2 expression, a transcription factor for antioxidant enzymes, and a possible link between oxidative stress, neuroinflammation and autophagy mechanisms, indicated significant overexpression ( P< 0.005) in the hippocampus and frontal cortex of the açaí-fed rats. Furthermore, significant activation of endogenous antioxidant enzymes GST and SOD were also observed in the açaí-fed animals when compared to control. Analysis of autophagy markers such as p62, phospho-mTOR, beclin1 and MAP1B-LC3 revealed differential expression in frontal cortex and hippocampus, mostly indicating an upregulation in the açaí-fed rats. Discussion: In general, results were more profound for EP than EO in hippocampus as well as frontal cortex. Therefore, an açaí-enriched diet could possibly modulate Nrf2, which is known to modulate the intracellular redox status, thereby regulating the ubiquitin-proteosomal pathway, ultimately affecting cognitive function in the aging brain.